Shear strength of reinforced concrete beams strengthened by P.B.O. fiber mesh under loading - Blikharskyy Zinoviy; Khmil Roman; Vegera Pavlo (MATEC Web of Conferences, 2017)
This article presents experimental study of sheer strength of reinforced concrete beams without transverse steel reinforcement, which strengthened by composite materials. The feature of tests is that the beams’ strengthening is made under simultaneous action of loading. The research program involves a series of test beams with size 2100 × 200 × 100 mm and which contains control sample and three reinforced samples by reinforcing FRCM system. FRCM system consisting of two components: mineral mortar based on modified cement Ruredil X Mesh M750 and reinforcing P.B.O. fiber mesh Ruredil X Mesh Gold (Italy). The strength research of test samples was carried out with the shear distance to effective depth ratio a/d = 2. The strengthening loading levels were selected at 0.0, 0.3, 0.5 from shear strength of non strengthened control sample. As a result of experimental studies we found that during strengthening design the inclined cross section of beams we should take into account the existing level of loading. Using the strengthening system Ruredil X Mesh Gold the strengthening effect is reduced at 2.8 to 2.9 times while the existing level of loading increase from 0 to 50%.